(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Аннототция. Гематологические изменения при отравлении рыб некачественными кормами характеризовались снижением количества гемоглобина, числа эритроцитов и числа лейкоцитов, повышением скорости оседания эритроцитов. Annotation. Hematological changes in fish poisoning with low-quality feed were characterized by a decrease in the amount of hemoglobin, the number of erythrocytes and the number of leukocytes, and an increase in the erythrocyte sedimentation rate.